Dynamics of Interleukin-10 Levels in Chronic Rhinosinusitis with/without Allergy - Abdul Qadar Punagi; Sutji Pratiwi Rahardjo (The Prodia Education and Research Institute (PERI), 2015)
BACKGROUND: Rhinosinusitis occurs when the lining of the nasal and sinuses gets inflamed, infected or irritated, become swollen, and create extra mucus, the swollen lining may also interfere with drainage of mucus. Chronic rhinosinusitis (CRS) is a more persistent problem that requires a specific treatment approach. Aim of this study was to determine changes in interleukin (IL)-10 as an anti-inflammatory cytokines in allergic and non-allergic CRS at Makassar. METHODS: A prospective cohort study was designed to assess the level of IL-10 for three times during two weeks of therapy. Medication of Cefadroxil 500 mg 2x1, Pseudoephedrine 30 mg 2x1, Terfenadine 40 mg 2x1 and Methylprednisolone 4 mg 3x1, was conducted during two weeks for 13 subjects in allergic CRS group and 12 subjects in non-allergic CRS group. Results were statistically analyzed with student t-test and paired t-test.RESULTS: The changes in levels of IL-10 in allergic CRS group were increased, but not significant (5.293 to 5.769, p=0.058), and in non-allergic CRS group were decreased, but not significant (6.125 to 5.475, p=0.103). CONCLUSION: The serum levels of IL-10 were not significant increased in allergic CRS group and not significant decreased in non-allergic CRS group. KEYWORDS: interleukin-10, chronic rhinosinusitis, allergy, cefadroxil, pseudoephedrine, terfenadine, methylprednisolone